Bimbingan Konseling Dalam Menyikapi Perubahan Fisik dan Emosi Remaja - cahyo ansory, alfi lail; asrori, dimas; Muslih, Misbakhul; al arifi, tuhvatul afandi; Izzulhaq, Muhammad Iqbal; laela, alfi nur; Fathoni, Tamrin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to analyze the role of counseling in helping adolescents deal with physical and emotional changes during puberty, explain the impact of these changes on mental and social well-being, develop effective strategies in counseling, evaluate its effectiveness in improving self-understanding, emotional management, and social skills of adolescents, and encourage the implementation of more optimal counseling in schools, families, and communities. The library method in this study was carried out by collecting, reviewing, and analyzing various relevant written sources, such as books, scientific journals, research articles, and academic reports that discuss theories of adolescent development and the effectiveness of counseling in improving mental and social well-being of adolescents, in order to formulate evidence-based recommendations regarding best practices in counseling for adolescents. Effective counseling plays an important role in helping adolescents deal with physical and emotional changes during their transition. This program has been shown to improve self-understanding, reduce anxiety and depression levels, and develop emotional management skills through relaxation techniques and open communication. In addition, counseling also contributes to improving adolescents' social skills, so that they are more confident in interacting with their surroundings.